Application of PjBL Learning Model and TPACK-Based Learning Media to Improve IPAS Learning Outcomes - Dewi, Fitria; Nurkholis, Nurkholis; Sholihati, Vivit (Jurnal Edusci, 2023)
The goal of this research is to define the stages involved in applying the model of ProjectBased Learning (PjBL) in order to improve student learning results, particularly in scientific topics.The goal of this research is to define the stages involved in applying the model of Project BasedLearning (PjBL) in order to improve student learning results, particularly in scientific topics. Datacollection techniques used test and non-test techniques. The data analysis methods employed includedescriptive, qualitative, and quantitative. The findings revealed that the adoption model of PjBL withthe 4C, HOTS, and TPACK techniques improved learning outcomes in grade 4 pupils at SDN 4Kenanga. This is demonstrated by the rise in average student achievement observed in cycle 2. Incycle 1, the average individual value of 60.6 with 20 participants (67 percent) in the incompletesection of KKM calculated is 70, indicating that student achievement have not improved. While incycle 2, there is an improvement in student achievement from an average value of 78 to as many as23 or (76 percent) pupils finishing.